IMPROVEMENT OF MANAGEMENT SYSTEMS, TRACTION MOTORS OF DIESEL LOCOMOTIVES - Shapran, E. N. (Science and Transport Progress, 2005)
In the article there are results of analysis the possibility of the construction microprocessor system of the main electric drive which to improve tractive-energetic characteristics of locomotives.